Hyperbranched self-assembled photoanode for high efficiency dye-sensitized solar cells. Issue 113 (30th October 2015) - Passoni, Luca; Giordano, Fabrizio; Zakeeruddin, Shaik M.; Grätzel, Michael; Di Fonzo, Fabio
Abstract : The photoanode morphology is key for improving photovoltaic performance of dye-sensitized solar cells. Abstract : The photoanode morphology is key for improving photovoltaic performance of dye-sensitized solar cells. On one side, light harvesting depends on its capability of both chemisorbing high quantity of dye and affecting the flow of light in order to enhance its optical thickness. On the other, electron transport is influenced by the crystalline domain size and shape. In this work we report on how the morphology of self-assembled hyperbranched quasi 1D nanostructures can be engineered by physical vapour deposition in order to maximize light harvesting and electron transport. High specific surface area was achieved by optimizing crystalline domain size. This way, quasi 1D nanostructures allow for high light harvesting efficiency, broadband and intense light scattering while sustain significant decrease in electron transport time. Hyperbranched nanostructures photoanodes led to a power conversion efficiency over 9%.